2023
DOI: 10.1002/jex2.107
|View full text |Cite
|
Sign up to set email alerts
|

Human red blood cells release microvesicles with distinct sizes and protein composition that alter neutrophil phagocytosis

Getulio Pereira de Oliveira,
Joshua A. Welsh,
Brandy Pinckney
et al.

Abstract: Extracellular vesicles (EVs) are membrane‐bound structures released by cells and tissues into biofluids, involved in cell‐cell communication. In humans, circulating red blood cells (RBCs), represent the most common cell‐type in the body, generating daily large numbers of microvesicles. In vitro, RBC vesiculation can be mimicked by stimulating RBCs with calcium ionophores, such as ionomycin and A23187. The fate of microvesicles released during in vivo aging of RBCs and their interactions with circulating cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 71 publications
0
1
0
Order By: Relevance
“…From the morphological findings, the sheading of extracellular vesicles is a key observation. It has been reported that erythrocyte extracellular vesicles can alter neutrophil’s phagocytic behavior depending on their size and content [ 74 ]. Extracellular nanovesicles released by human erythrocytes have been considered to play different roles in physiological, pathological, and even immune processes; their formation has been linked to intracellular calcium level increases, ATP depletion, or oxidative stress conditions [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…From the morphological findings, the sheading of extracellular vesicles is a key observation. It has been reported that erythrocyte extracellular vesicles can alter neutrophil’s phagocytic behavior depending on their size and content [ 74 ]. Extracellular nanovesicles released by human erythrocytes have been considered to play different roles in physiological, pathological, and even immune processes; their formation has been linked to intracellular calcium level increases, ATP depletion, or oxidative stress conditions [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…To estimate the relative abundance of circulating EV subsets with respect to their cell origin, we used established markers for the immunophenotyping by flow cytometry (Kalina et al 2019;Grant et al 2021;de Oliveira et al 2023;Berckmans et al 2019;Spurgeon and Frelinger 2022). We designated CD235a+ subsets as erythrocyte EVs, CD41+ and PAC1+ subsets as platelet EVs, and CD61+, CD31+, and CD62P+ subsets as originating from platelets or endothelial cells.…”
Section: Quantification Of Ev Populations With Respect To Their Cell ...mentioning
confidence: 99%